2005
DOI: 10.1002/srin.200506116
|View full text |Cite
|
Sign up to set email alerts
|

Precise Material Properties as a Prerequisite for FE-Analysis of the Hydroforming of Tailored Welded Blanks

Abstract: Tailored welded blanks are already used in the series production of deep drawn parts, and are now considered also for other forming technologies, like for example hydroforming. As new materials come into the market, also their combinations in the production of new tailored welded blanks increase, improving on the one hand the possibilities of matching material and functional requirements, but making the material characterisation more difficult on the other hand. For this reason new methods for a fast, precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…In most forming processes like stamping or bending, it is suffi cient to adopt the constant friction coeffi cient for contact between the base metal and the tool. Tolazzi and Merklein showed that considering friction coeffi cients of the weld seam could considerably improve the accuracy of the FEM model (Tolazzi and Merklein, 2005).…”
Section: Finite Element Methods (Fem) Modeling Of the Welded Zonesmentioning
confidence: 99%
“…In most forming processes like stamping or bending, it is suffi cient to adopt the constant friction coeffi cient for contact between the base metal and the tool. Tolazzi and Merklein showed that considering friction coeffi cients of the weld seam could considerably improve the accuracy of the FEM model (Tolazzi and Merklein, 2005).…”
Section: Finite Element Methods (Fem) Modeling Of the Welded Zonesmentioning
confidence: 99%
“…Ghoo et al used tensile tests for the evaluation of work hardening and strength indexes of weld metal [8]. They concluded that normalized workhardening indexes of the welded metals are lower than the mean value of those of the parent materials (further approved by results of Tolazzi and Merkein [17]). However, the strength indexes of the welded metals are higher than the mean value of those of the base metals.…”
Section: Mechanical Properties Of Twbsmentioning
confidence: 99%